PENGATURAN POLISI TIDUR DALAM UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN UMUM - Deva Ganika Murtha, Luh Ketut; Pasek Diantha, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013, 2013)
This paper entitled “ARRANGEMENTS TRAFFIC BUMPS Act NO.22 OF 2009 ON TRAFFIC AND PUBLIC TRANSPORT”. This paper uses normative analysis method. Traffic bumps presence in Indonesia was very helpful in air traffic safety because it can reduce the number of traffic accidents. Making the bumps as a means of control and the safety of road users. Called traffic bumps because it function is almost the same with the police they both warned that the streets of every passing vehicle to be careful and slow down.
Keywords: Accidents, Traffic Bumps, Traffic